The Differences of Social Work Process in Faith-related and Secular NGOs - Renevė, Giedrė; Dunajevas, Eugenijus (Socialinė teorija, empirija, politika ir praktika, 2014)
UAB “Tango reklama”Laisvės avenue 60, Vilnius, 05120giedre.reneve@gmail.comVilnius UniversityDepartment of Social WorkUniversiteto str. 9/1, Vilnius, 01513eugenijus.dunajevas@fsf.vu.ltSummaryWe analysed social work process in faith-related and secular NGOs. The objective of the study was to reveal the differences of social work process. We define social work process as an algorithm of actions that is proceeded in order to solve social and personal problems. There are five stages of social work process. At each stage the participants of social work organisation perform certain actions. In order to find out the differences of social work process, the actions were compared in faith-related and secular NGOs. The results of data analysis reveal the significant differences of social work process in secular and faith-related social work NGOs.Keywords: Social work process, non-governmental organisations, faith-related and secular organisations.